The Impact of Cultural Tourism on Tourism Progress and Local Original Income: An SDGs Perspective in Alor Regency - Rahmat Laan; Syarifuddin Darajad; Ahmad Atang; Sari Zulfiana Hasan; St. Rukaiyah (Profetika: Jurnal Studi Islam, 2026)
Objective: This study aims to analyze the influence of cultural tourism on tourism progress and Regional Original Income (PAD) in the tourism sector and examine the mediating role of tourism progress from the perspective of Sustainable Development Goals (SDGs) in Alor Regency. Theoretical Framework: This study is based on the theory of cultural tourism, sustainable tourism development, and regional economic development that places culture as a strategic asset in increasing destination competitiveness and regional fiscal capacity. Literature Review: Although various studies have discussed the economic benefits of cultural tourism, regional tourism development, and PAD in the tourism sector in island regions are still limited. Method: The study used a quantitative approach with a cross-sectional explanatory design. Data were obtained from 60 tourism stakeholders through purposive sampling and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). Results: Cultural tourism has a positive and significant effect on tourism progress (β=0.507; p<0.001) and PAD in the tourism sector (β=0.597; p<0.001). Tourism progress also has a positive effect on the tourism sector's PAD (β=0.252; p=0.004) and partially mediates the relationship between cultural tourism and PAD (β=0.128; p=0.033). The effect size value (f²=0.620) indicates that cultural tourism is the main determinant of increasing the tourism sector's PAD. Implications: These findings provide an empirical basis for formulating cultural tourism development policies that support the achievement of SDGs 8, SDG 11, and SDG 17. Novelty: This study offers an empirical model that integrates cultural tourism, tourism progress, and tourism sector PAD in a single SDGs-based analytical framework in the context of an archipelagic region, which is still relatively rarely studied in Indonesian tourism literature.